ABDULLAH QADIRI’S "O’TKAN" DAYS IN THE NOVEL TRAGIC LOVE STORY - Umarova Munavvar Nurmuhammedovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In the article famous The most famous writer is Abdulla Qadiri from his works one is ’’ Passed days ’’ novel , in it images system , humanity and Uzbek characteristics , people between sincere relationship , their between human feelings about word goes​